Efektivitas Penerapan Surat Edaran Mahkamah Agung (SEMA) No. 3 Tahun 2023 Terhadap Penanganan Perkara Perceraian di Pengadilan Agama Bima Kelas 1A - Bima, Fajar; Syarif Hidayatullah; Hikmah (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This study aims to analyze the implementation and effectiveness of Supreme Court Circular Letter (SEMA) No. 3 of 2023 in handling divorce cases at the Bima Class 1A Religious Court, especially in accelerating the case settlement process. This research uses a descriptive qualitative approach with a focus on data collection through in-depth interviews with judges and court clerks, as well as analysis of legal documents and related literature. The results show that SEMA No. 3 of 2023 has had a positive impact in accelerating the settlement of divorce cases, reducing the processing time from 3-4 months to 1-2 months for cases that meet the requirements. This policy also helps to equalize judges' perceptions through clear parameters, such as the requirement of a minimum 6-month separation and proof of no hope of living together. However, there is dualism in interpretation in its application, especially regarding whether the duration of the dispute is sufficient or whether it must be accompanied by evidence of separation from home. In addition, socialization to the public still needs to be improved so that applicants understand the importance of preparing evidence from the start. Overall, SEMA No. 3 Year 2023 proved effective in creating a more efficient and scalable divorce court system, although more detailed technical guidelines, intensification of legal counseling, and periodic evaluations are needed to maximize its implementation. This study recommends harmonization of interpretation at the court level as well as an educative approach to the community to strengthen the effectiveness of this policy in the future.